Field-based supercritical fluid extraction and immunoassay method for determination of organic contaminants - Rigou, P (Cranfield University, 2003)
The contamination of soils, particularly by organic pollutants at industrial sites, has required the development of accurate methods of analysis to determine the nature and concentration of the pollutants, thereby allowing appropriate risk assessments and remedial strategies to be implemented. Conventional methods for site assessment generally entail extensive sampling across the whole site, with subsequent sample despatch to a centralised laboratory, where complex, solvent intensive procedures, such as Soxhlet extraction and GC-MS analyses are performed. Since such processes are laborious, expensive, and time-consuming, there has been an increasing demand for rapid and reliable field-based analytical methods for the low-cost and efficient extraction and analysis of organic pollutants from contaminated sites. This thesis describes the development of a field-compatible supercritical fluid extraction (SFE) device and method for extraction of organic contaminants from soil. SFE was chosen due to its reported high extraction efficiency, selectivity and environmentally friendly nature due to the usage of supercritical fluids as opposed to liquid solvents. A compact 72(W)xS7(D)xSO(H) cm, easily-transportable and user-friendly device was developed, based on the use of a reciprocating pump and back pressure regulator system. The optimised method yielded an average extraction recovery of 80% for total polycyclic aromatic hydrocarbons (PABs) when compared to the well-validated laboratory-based Soxhlet extraction method. Tests were performed on a range of natural samples with varying water content (0- 32% w/w) without any sample pre-treatment. In comparison, the only commercially available competing field method, based on solvent shake extraction, yielded recovery values of 20-70% coupled with poor precision. The thesis then describes the optimisation of a field applicable method for analysis of the SFE extracts, based on enzyme linked immunosorbent assays (ELISAs), a method offering speed, low cost and low solvent consumption. Available as a test kit, it was readily amenable to on-site usage requiring only simple equipment. Assay optimisation using an EPA sanctioned P AH immunoassay test kit demonstrated that the kit could function in methanolic SFE extracts diluted in buffer, hence allowing the direct analysis of total P ABs in SFE extracts with minimum sample preparation. Cross-reactivity from parent compounds was found to be an issue for the generation of quantitative data. Nevertheless, the method served as a reliable semi-quantitative technique for rapid screening of P AH levels in the SFE extracts of natural samples obtained from field-based tests. Poor performance of the solvent-shake extraction method linked to immunoassay further vindicated usage of the newly developed field-based SFEI immunoassay method. The thesis concludes by reporting on the successful field-based trials of the coupled SFE/immunoassay method. The SFE system shows promise as a valid tool for the rapid and efficient on-site monitoring of organic contaminants in soil matrices, providing an innovative and alternative approach to the commonly deployed solvent shake extraction method. The combined field-based SFElimmunoassay method is of benefit for the rapid low cost assessment of site contamination, allowing site owners and consultants alike to make rapid and informed decisions regarding site characterisation, monitoring and remediation without recourse to expensive and time consuming laboratory analyses.